Plasmatic and Platelet Anti-Plasmins and Anti-Activators - den Ottolander, G. J. H; Leijnse, B; Cremer-Elfrink, H. M. J (Thrombosis and Haemostasis, 1967)
Direct antiplasmin and anti-urokinase can be measured with artificial clots to which plasma, serum or platelet suspension is added incubated in plasmin or urokinase respectively. Whilst only 3% of the total antiplasmin in the blood is present in the platelets, there is 40% of the total antiurokinase present in the platelets. The properties of this thrombocytic anti-urokinase are discussed. Only 60% is soluble in water. By heating this solution the inhibiting effect increases. Platelet anti-activator is also active against other activators but has not the same properties as anti-urokinase. Implications of these findings are discussed.